PENGELOLAAN PENDIDIKAN KARAKTER DI PONDOK PESANTREN MUHAMMADIYAH â€œMIFTAKHUL â€˜ULUMâ€ PEKAJANGAN PEKALONGAN - Aulia S, Muhammad Fakhrial (PKn Progresif, 2015)
Generally, this research is aimed to describe character education management at ?Miftakhul ?Ulum? Muhammadiyah boarding school of Pekajangan Pekalongan. This research is ethnography descriptive research. Research subject, teaching-learning process, runs in natural setting and there is no researcher?s special treatment to control. Research conclusion shows that character education management indoor and outdoor has 3 (three) steps: planning, actuating, and evaluating. Obstacles in character education management: less commitment teachers, indiscipline students, and the limited facilities and infrastructure. Solutions to cover obstacles are Baitul Arqam for teachers, motivating students continually, and build new local.